Base-Metal-Catalyzed Olefin Isomerization Reactions - Liu, Xufang; Li, Bin; Liu, Qiang (Synthesis, 2019)
The catalytic olefin isomerization reaction is a highly efficient and atom-economic transformation in organic synthesis that has attracted tremendous attention both in academia and industry. Recently, the development of Earth-abundant metal catalysts has received growing interest owing to their wide availability, sustainability, and environmentally benign nature, as well as the unique properties of non-precious metals. This review provides an overview of a broad range of base-metal-catalyzed olefin isomerization reactions categorized according to their different reaction mechanisms.1 Introduction2 Base-Metal-Catalyzed Olefin Isomerization Reactions3 Base-Metal-Catalyzed Cycloisomerization Reactions4 Conclusion
Keywords: base metals; homogeneous catalysis; olefin isomerization; cycloisomerization; reaction mechanism